2003
DOI: 10.1111/1540-6261.00593
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Analysts' Target Prices: Short‐term Informativeness and Long‐term Dynamics

Abstract: Using a large database of analysts' target prices issued over the period 19971 999, we examine short-term market reactions to target price revisions and long-term comovement of target and stock prices.We ¢nd a signi¢cant market reaction to the information contained in analysts' target prices, both unconditionally and conditional on contemporaneously issued stock recommendation and earnings forecast revisions. Using a cointegration approach, we analyze the long-term behavior of market and target prices. We ¢nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
193
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(222 citation statements)
references
References 42 publications
(56 reference statements)
27
193
1
1
Order By: Relevance
“…Da and Schaumburg [2011] documented that industry relative valuations, which are implicit in analyst target prices, provide investors with valuable information, although the implied absolute valuations themselves are much less informative. More closely related to our study, Brav and Lehavy [2003] found a significant market reaction to the information contained in analyst target prices, both unconditionally and conditional on contemporaneously issued stock recommendation revisions and earnings forecast revisions. 1 Although Brav and Lehavy generally found on average no significant excess returns in the periods subsequent to target price revisions, they did show that the market underreacts to target price revisions conditional on certain recommendation revisions.…”
Section: Literature Reviewsupporting
confidence: 83%
See 1 more Smart Citation
“…Da and Schaumburg [2011] documented that industry relative valuations, which are implicit in analyst target prices, provide investors with valuable information, although the implied absolute valuations themselves are much less informative. More closely related to our study, Brav and Lehavy [2003] found a significant market reaction to the information contained in analyst target prices, both unconditionally and conditional on contemporaneously issued stock recommendation revisions and earnings forecast revisions. 1 Although Brav and Lehavy generally found on average no significant excess returns in the periods subsequent to target price revisions, they did show that the market underreacts to target price revisions conditional on certain recommendation revisions.…”
Section: Literature Reviewsupporting
confidence: 83%
“…While Brav and Lehavy [2003] provided some initial evidence on how investors respond to revisions in target prices, as they cautioned in their article, their sample period (1997)(1998)(1999) coincides with the highs of the bull market in the United States, which might be viewed as an historically unusual period. Therefore, their results may not be generalizable to other periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this respect, results which indicate a significant association between the excess of returns regarding the recommendation issuance and the recommendation level are presented. Other studies in the field, such as the ones carried out by Barber, Lehavy, McNichols and Trueman (2001); Brav and Lehavy (2003); Stickel (1995);and Womack (1996), suggest that target prices are significantly associated with excess returns in the period of the event.…”
Section: Introductionmentioning
confidence: 93%
“…The previous literature points to analysts as information intermediaries who act between companies and investors, and as one of the responsible agents for reducing information asymmetry. Some studies observed that target prices are significantly associated with exceeding returns in the period of the event (e.g., Barber, Lehavy, McNichols, & Trueman, 2001;Brav & Lehavy, 2003;Stickel, 1995;Womack, 1996).…”
Section: Final Considerationsmentioning
confidence: 99%
“…But it should be noted that we repeated all of the tests on the two other performance measures as well, and the results were qualitatively consistent across all three performance measures. Furthermore, because the distributions of the ratio variables are conducive to outliers, following the standard empirical finance and accounting literature on the treatment of outliers, such as Brav and Lehavy (2003) and Durnev and Kim (2005), we winsorized the data at the 1% and 99% levels. 7 Our results are robust to whether we perform such winsorization.…”
Section: Variable Definitionsmentioning
confidence: 99%